2018
DOI: 10.21324/dacd.415081
|View full text |Cite
|
Sign up to set email alerts
|

Assessing and Mapping Erosion Risk for Velikoy Sub-watershed within Coruh River Basin in Turkey

Abstract: Vegetation on earth surface is the integral part of the world ecosystems in functioning for varying spatial and temporal scales. Along with other benefits, land-use as a forest can dramatically reduce the soil erosion and water pollution by protecting the soil surface from erosive effects of rainfall. The objective of this study was to determine rill/interrill (surface) erosion risk by using the RUSLE equation for Velikoy sub-watershed (417 km 2) which has rich forest-resources within the Coruh River Basin loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
0
0
Order By: Relevance
“…The soil sensitivity factor is closely related to the strength of the soil (Tufekcioglu et al, 2018). The higher the level of erodibility, the higher the level of landslide risk.…”
Section: Soil Erodibility Factormentioning
confidence: 99%
“…The soil sensitivity factor is closely related to the strength of the soil (Tufekcioglu et al, 2018). The higher the level of erodibility, the higher the level of landslide risk.…”
Section: Soil Erodibility Factormentioning
confidence: 99%
“…The SDR was calculated 0.12. The sediment yield or soil loss was calculated by simply multiplying the soil erosion (A) obtained from the RUSLE with the SDR value (Tufekcioglu et al 2018).…”
Section: Sediment Delivery Ratio (Sdr)mentioning
confidence: 99%
“…As per Prasannakumar et al (2011), the average erosion rate for the Siruvani river watershed in Attapady valley, Kerala, India, is 14.917 t.ha -1 .yr -1 , with 5.76% (1,184 hectares) of the land lying under the severe soil erosion zone and 11.50% being under the high-erosion zone. A study by Tufekcioglu et al (2018) in the Coruh River Basin of Turkey found that the Velikoy sub-watershed had an average surface soil loss rate of 3.9 t ha-1 yr-1, with 8.2% of the area at high or very high risk for potential erosion. Another study by Sheikh et al (2011) observed that mean soil erosion rate of 12.2 t.ha -1 .yr -1 at the Upper South Koel Basin, Jharkhand, India.…”
Section: Estimation Of Net Soil Erosionmentioning
confidence: 99%